Examining the validity of divine nature for religious experience in the perspective of Ayatollah Javadi Amoli - yaser hashemi; ahmad valiee (حکمت اسرا)
One of the special ways to communicate between the right and creation is the discussion of the "divine nature" of man. Therefore, in this article, we try to express the nature and types of religious experiences, especially Ayatollah Javadi Amoli's view of the divine nature of man; Care should be taken to examine how this point of view can be validated under various religious experiences. With the investigation done by the analytical-documentary method, and with the comparison made between religious experiences and divine nature from his point of view, it is clear that the nature that is presented from the perspective of Ayatollah Javadi is one of the examples of religious experience and one of its types. According to his view on this matter, it is placed under mystical experiences, both in its general sense and in its specific sense.